Trempealeau County conservation survey report - Janke, James; Trechter, David (My University, 2014)
The purpose of this study was to gather information and opinions about conservation issues from Trempealeau County farmland owners.
34 p.
Keywords: Agricultural conservation--Wisconsin--Trempealeau County; Land use--Wisconsin--Trempealeau County; Farms--Wisconsin--Trempealeau County